The disparities in health insurance ownership of hospital-based birth deliveries in eastern Indonesia - Agung Dwi Laksono; Ratna Dwi Wulandari; Zuardin Zuardin; Nopianto Nopianto (BMC, 2021)
Abstract Background Development in Eastern Indonesia tends to be left behind compared to other Indonesian regions, including development in the health sector. The study aimed at analyzing the health insurance ownership disparities in hospital delivery in Eastern Indonesia. Methods The study draws on secondary data from the 2017 Indonesia Demographic and Health Survey. The study population was women aged 15-49 years who had given birth in the last five years in Eastern Indonesia. The study analyzes a weighted sample size of 2299 respondents. The study employed hospital-based birth delivery as a dependent variable. Apart from health insurance ownership, other variables analyzed as independent variables are province, residence type, age group, marital status, education level, employment status, parity, and wealth status. The final stage analysis used binary logistic regression. Results The results showed that insured women were 1.426 times more likely than uninsured women to undergo hospital delivery (AOR 1.426; 95% CI 1.426-1.427). This analysis indicates that having health insurance is a protective factor for women in Eastern Indonesia for hospital delivery. There is still a disparity between insured and uninsured women in hospital-based birth deliveries in eastern Indonesia. Insured women are nearly one and a half times more likely than uninsured women to give birth in a hospital. Conclusion The study concludes that there are health insurance ownership disparities for hospital delivery in eastern Indonesia. Insured women have a better chance than uninsured women for hospital delivery.